Efeitos do silenciamento de duas Triptofanil-tRNA sintetases de Trypanosoma brucei mediante RNA de interferência - Sánchez, Liliana Torcoroma García (Universidade Federal de São Carlos, 2001)
The parasitic Trypanosoma brucei is the causative agent of African Trypanosomiasis (sleeping sickness) in humans, and nagana in animals and is responsible for heavy socioeconomic losses in most countries of sub-Saharan Africa. Therapy against sleeping sickness is unsatisfactory because the toxicity and arising of the drug resistant parasites. Trypanosomatids contain a single mitochondrion, the kinetoplast, whose genetic code deviates from the universal code where a UGA stop codon is used as a Trp codon. A single nuclear-encoded tRNATrp(CCA), that can decode the canonical Trp codon, is used by both the nucleus and mitochondria genes. A C to U editing event at position 34 of tRNATrp(CCA) changes the anticodon from CCA to UCA allowing the decoding of the UGA stop codon to Trp from the mitochondrial genes. We have identified two different nuclear-encoded tryptophanyl-tRNA-synthetase (WARSs) genes (one cytoplasmic (WARS1) and the other to the kinetoplast (WARS2)) in both Leishmania and Trypanosoma cells. With the purpose to validate the mitochondrial WARS enzymes of trypanosomatids, as potential drug targets, we performed gene silencing (RNAi) experiments with both WARSs forms from T. brucei. In the conditions tested, the expression of dsRNA from a dual promoter system generated potent RNA silencing, leading to clear phenotypes characterized by morphologic alterations, severe growth inhibition, reduction in the levels of oxygen consumed (only TbWARS2) and cellular death. The efficiency and specificity of silencing were estimated by quantitative PCR and significant modifications of the specific amount of TbWARSs mRNA were evidenced.
Keywords: Genética; Evolução; Tripanosomíase africana; Kinetoplastídeos; CIENCIAS BIOLOGICAS::GENETICA